Development of a Capacitive Sensing Module to Detect the Concentration of Isopropyl Alcohol for Covid-19 Disinfection Using Small Capacitance to DC Converter - Witsarut Sriratana; Manasnit Faijaree; Lerdlekha Sriratana; Sutham Satthamsakul (My University, 2024)
This paper presents the development of a sensing module for analyzing the concentration of disinfectant alcohol commercially available in Thailand during the Covid-19 epidemic situation to ensure the ingredients and percentage concentration by focusing on simplicity, low cost with reliable performance. Under the basic physical structure of the capacitance change [1]–[5], it consists of a New Sensor Module developed to fully interface with the small capacitance to DC converter for capacitive sensor [2] model. Inside the sensing structure, there were 2 modules of metal conductors. Each conductor was 3 mm. thick, placed in parallel with a fixed distance between the module of 1 mm. The cross-sectional areas of the plates of those two modules were different in order to compare the efficiency of the detector developed. The cross-sectional areas of the plates of Module A and B were 4 cm2 and 1 cm2, respectively. Experiments were performed with 3 concentrations of alcohol, 65%, 70% and 75%, to enhance the concentration detecting performance of the sensing module developed. The signal conditioning was generated from a small capacitance to DC converter for capacitive detection with a frequency of 100 kHz, which was the most suitable frequency for exciting the capacitance change which was the capacitive reactance of the alcohol used in this study. From experiments, it was found that the sensing module with a small cross-sectional conductive material would provide more accurate results in terms of linearity and repeatability. The errors were less than 2.72% compared to the module with a large cross-sectional conductor material which would have an error up to 4.73%.
Keywords: Analytical Chemistry and Sensors; Advanced Chemical Sensor Technologies; Gas Sensing Nanomaterials and Sensors